(untitled) (Филолошки студии, 2019)
By asserting that space has been thoroughly overlooked within postcolonial theory, despite all the obvious reasons that point to its significance, the author of the article tries to determine reasons for such a paradox drawn mostly upon Edward Soja’s book Postmodern Geographies. Since space to which postcolonial theory is being applied is becoming ever more expansive (the reasons for which are also explored in the article), the need to include space seems to be increasingly growing, both in terms of ontology and in terms of epistemology. By referring to Nikola Petković’s book A Central Europe of Our Own, the author tries to show that by deploying a strictly temporal perspective, there always exists the danger of bringing postcolonial theory into perfect accordance with some very seductive trends of globalization, a modus operand through which the already mentioned theory begins obscuring those relations of power that it tried to undermine in the first place. The article ends by exploring the concept of space, or rather of geography as something that can help understand power relations not only between nations but also within them, much along the lines of linking, and not strictly dividing one country or another, sustaining the necessity to turn hybrid space, that postcolonial theory favours despite it being its greatest downfall, into real place.